The Influence of Experiential Marketing and Promotion on Repurchase Intention of Starbucks in Surabaya - Bryan Johar Ilham Alam; Sugeng Purwanto (East Asian Journal of Multidisciplinary Research, 2023)
This research aims to analyze the influence of Experiential Marketing and Promotion on Repurchase Interest in Starbucks products in Surabaya. The method that applied in this research is a quantitative approach using the accidental sampling technique. The research sample is consisted of 104 respondents who had purchased Starbucks products. The data for this research was collected through filling out questionnaires distributed to visitors. Data analysis uses the Partial Least Square (PLS) model. The findings of this research indicate that Experiential Marketing and Promotion have a significant influence on Repurchase Intention among Starbucks customers in Surabaya.